2009
DOI: 10.1016/j.envpol.2008.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene uptake by Medicago sativa L. under the influence of an arbuscular mycorrhizal fungus

Abstract: Colonization by an arbuscular mycorrhizal fungus promoted root uptake and decreased shoot uptake of phenanthrene by Medicago sativa L. a r t i c l e i n f o a b s t r a c tPhenanthrene uptake by Medicago sativa L. was investigated under the influence of an arbuscular mycorrhizal fungus. Inoculation of lucerne with the arbuscular mycorrhizal fungus Glomus etunicatum L. resulted in higher phenanthrene accumulation in the roots and lower accumulation in the shoots compared to non-mycorrhizal controls. Studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…This is in line with other results whereby Glomus etunicatum significantly increased PHE accumulation in roots of Medicago sativa [24]. These findings also agree with previous work on the effects of AM fungi on other organic pollutants including atrazine [30] and DDT [31].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in line with other results whereby Glomus etunicatum significantly increased PHE accumulation in roots of Medicago sativa [24]. These findings also agree with previous work on the effects of AM fungi on other organic pollutants including atrazine [30] and DDT [31].…”
Section: Discussionsupporting
confidence: 93%
“…Wu and Xia [37] observed that AM fungi could promote the volume and total absorption area of the root system. Wu et al [24] indicated that mycorrhizal roots consistently exhibited higher PHE adsorption than did non-mycorrhizal roots, although PHE adsorption onto roots only represented 0.6-3.23% of the total amount extracted from the roots growing in PHE-spiked soils. Therefore, although there was no direct evidence of any changes in root morphology and surface properties of the maize in the present study, it was suggested that the positive mycorrhizal growth of roots ( Fig.…”
Section: Soil Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…After being cultured in contaminated solutions, PAHs can also be absorbed through the roots and transported to the aboveground parts of the stems and leaves in various plant species, such as Oryza sativa L. (Jiao et al, 2007), Lolium multiflorum L. and Helianthus annus L. (Sneath et al, 2013). Transpiration drives the absorption and transport of PAHs from the underground part to the aboveground part (Tao et al, 2006;Mattina et al, 2003;Gao and Zhu, 2004;Wu et al, 2009). For instance, Wang et al (2012) proposed that PAHs are absorbed in the root epidermis before entering the pith and lateral roots.…”
Section: Study On the Absorption And Translocation Of Phe In P Vittatamentioning
confidence: 99%
“…[1][2][3] Although certain organic pollutants in the environment occur at trace levels, they can seriously threaten human health, either directly or indirectly, due to their toxicity and bioaccumulation. Therefore, the detection of trace environmental organic pollutants is necessary.…”
Section: Introductionmentioning
confidence: 99%